2017
DOI: 10.1002/nvsm.1603
|View full text |Cite
|
Sign up to set email alerts
|

“You can try to press different emotional buttons”: The conflicts and strategies of eliciting emotions for fundraisers

Abstract: In a competitive climate in which charities must increasingly rely on fundraising with the public, emotions such as hope, guilt, and fear are powerful tools that can be used strategically to secure donations or participation. This paper explores data from interviews with 23 fundraisers and voluntary sector workers, managers, and officials, to argue that decisions around how, why, and when to invest in the elicitation of emotion in fundraising are often difficult and conflicted, with some identifying a battle b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 20 publications
1
21
0
Order By: Relevance
“…However, our findings contradict this assumption. In line with previous criticism of face-to-face street fundraising (e.g., Bennett, 2013Bennett, , 2018Bennett & Barkensjo, 2005;Dean & Wood, 2017;Sargeant et al, 2012), we observed a diminution in the respondents' perceptions of an organization as well as their willingness to engage voluntarily. In fact, if an organization applies face-to-face street fundraising, many pedestrians seem to base their evaluation of the organization on the fundraising method rather than on organizational characteristics, at least when limited information is provided.…”
Section: Theoretical Implicationssupporting
confidence: 91%
See 1 more Smart Citation
“…However, our findings contradict this assumption. In line with previous criticism of face-to-face street fundraising (e.g., Bennett, 2013Bennett, , 2018Bennett & Barkensjo, 2005;Dean & Wood, 2017;Sargeant et al, 2012), we observed a diminution in the respondents' perceptions of an organization as well as their willingness to engage voluntarily. In fact, if an organization applies face-to-face street fundraising, many pedestrians seem to base their evaluation of the organization on the fundraising method rather than on organizational characteristics, at least when limited information is provided.…”
Section: Theoretical Implicationssupporting
confidence: 91%
“…Missing professionalism of these street fundraisers has led to critical voices regarding unethical behavior in the past couple of years (Ward, 2018). Dean and Wood (2017) found that particularly missing knowledge, the intentional provision of misinformation, and invasive approaches of chuggers cause negative feelings among potential donors, which may lead them to question whether these organizations are acting responsibly and can be trusted. Neitzsch (2012, p. 15) confirms that "the partially aggressive and dubious behavior of some fundraisers has brought a bad image to the whole sector."…”
Section: Literature Reviewmentioning
confidence: 99%
“…Charities have shifted from voluntary organisations that relied on altruism and goodwill to effectively operating as businesses in a crowded marketplace where they must compete for funding and public recognition (Hibbert, 1996). Charities have thus more actively courted potential donors and developed strategies to maximise fundraising (Dean and Wood, 2017). Appeals to negative emotions – such as guilt, fear and sadness – are particularly effective in motivating people to donate (Bagozzi and Moore, 1994), especially when coupled with an argument that a donation will help others (Fisher et al, 2008).…”
Section: Advocacy Research Policy-based Evidence and A Shifting Contmentioning
confidence: 99%
“…Yet, as Breeze (2017a) highlights, the role that fundraisers play in charitable giving is rarely studied. The small literature on this topic has been qualitative in nature and largely focused on the experiences of major donor fundraisers who develop one-on-one relationships with high-value donors and philanthropists (Alborough, 2017;Breeze & Jollymore, 2017;Dean & Wood, 2017).…”
Section: Individual Fundraisersmentioning
confidence: 99%
“…Successful fundraisers know how to use emotional levers when soliciting funds (Dean & Wood, 2017). Major donor fundraisers work as trusted brokers who build the donor's confidence in the charity and help the donor to understand the charity world (Breeze & Jollymore, 2017).…”
Section: Individual Fundraisersmentioning
confidence: 99%